PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN PERMAINAN MONOPOLI TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Dwi Retno Melathi; Lisa Virdinarti Putra (Universitas Ngudi Waluyo, 2022)
This study aims to determine the effect of the problem based learning model with the help of monopoly game learning media on the problem solving abilities of fourth grade students at SDN Jepatlor. This type of research is an experiment with a quasi-experimental method in the form of a nonequivalent control group design. The population is class IV SDN Jepatlor and the sample is class IV A as the experimental class and class IV B as the control class. The data analysis techniques used are normality test, homogeneity test and simple linear regression test. The results of this study indicate that there is an effect of using a problem based learning model with the help of a monopoly game on students' problem solving abilities. This is indicated by a significance result of 0.015 <0.05 using a simple linear regression test.